2018
DOI: 10.1126/scitranslmed.aau5516
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding regions are the main source of targetable tumor-specific antigens

Abstract: Tumor-specific antigens (TSAs) represent ideal targets for cancer immunotherapy, but few have been identified thus far. We therefore developed a proteogenomic approach to enable the high-throughput discovery of TSAs coded by potentially all genomic regions. In two murine cancer cell lines and seven human primary tumors, we identified a total of 40 TSAs, about 90% of which derived from allegedly noncoding regions and would have been missed by standard exome-based approaches. Moreover, most of these TSAs derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
436
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(456 citation statements)
references
References 69 publications
17
436
1
2
Order By: Relevance
“…It is becoming increasingly clear that aberrantly expressed tumor-rejection antigens (including peptides corresponding to genes of retroviral origin, which have been integrated into the genome at some stage during evolution) may be relevant for anticancer immune surveillance in mice as well as in humans. 49 Experimental evidence arises not only from mass spectrometry-based analysis of peptide presentation on MHC class I molecules, 43,49 but also from the results of therapeutic vaccination studies with peptides corresponding to aberrantly expressed antigens. 49,50 When considering human tumors, Miller et al have reported that polyomavirus-specific T cells may represent up to 21% of the T cell specificities within the tumor mass of Merkel cell carcinoma (MCC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming increasingly clear that aberrantly expressed tumor-rejection antigens (including peptides corresponding to genes of retroviral origin, which have been integrated into the genome at some stage during evolution) may be relevant for anticancer immune surveillance in mice as well as in humans. 49 Experimental evidence arises not only from mass spectrometry-based analysis of peptide presentation on MHC class I molecules, 43,49 but also from the results of therapeutic vaccination studies with peptides corresponding to aberrantly expressed antigens. 49,50 When considering human tumors, Miller et al have reported that polyomavirus-specific T cells may represent up to 21% of the T cell specificities within the tumor mass of Merkel cell carcinoma (MCC).…”
Section: Discussionmentioning
confidence: 99%
“…49 Experimental evidence arises not only from mass spectrometry-based analysis of peptide presentation on MHC class I molecules, 43,49 but also from the results of therapeutic vaccination studies with peptides corresponding to aberrantly expressed antigens. 49,50 When considering human tumors, Miller et al have reported that polyomavirus-specific T cells may represent up to 21% of the T cell specificities within the tumor mass of Merkel cell carcinoma (MCC). 51 Besides virally driven tumors (e.g., MCC and HPV-derived malignancies), 20 potentially immunogenic endogenous retroviruses have recently been reported in clear-cell renal cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Often, MS-based immunopeptidomic discoveries are limited to the standard, available protein sequence database, usually containing only annotated protein-coding sequences. Recently, several studies have included protein sequences derived from the translation of transcripts identified from RNA-Seq, or from ribosome profiling, into MS-based searches 9,[23][24][25][26][27][28] . Overall, these studies warrant further development in many key aspects: Importantly, elevated false discovery rates (FDRs) for the non-canonical space can occur when MS reference data are populated with protein sequences derived from all potential three-or six-frame translations of transcribed regions 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the peptides derived from noncoding regions accounted for approximately 10% of the MHC class I ligands in human B cells. Moreover, the group recently reported that cancer cells also present those cryptic peptides by MHC class I, which induced host anti‐cancer CD8 + T‐cell responses in mouse models . Our group independently searched the HLA class I ligandome of human colon cancer cell lines and a variety of primary cancer tissues and found that approximately 1% of the HLA ligands arose from noncoding regions (unpublished data).…”
Section: Noncoding Region‐derived Cancer Antigensmentioning
confidence: 96%
“…Moreover, the group recently reported that cancer cells also present those cryptic peptides by MHC class I, which induced host anti-cancer CD8 + T-cell responses in mouse models. 36 Our group independently searched the HLA class I ligandome of human colon cancer cell lines and a variety of primary cancer tissues and found that approximately 1% of the HLA ligands arose from noncoding regions (unpublished data). These findings support the hypothesis of translation from, if not all, allegedly noncoding RNAs.…”
Section: Noncoding Region-derived Cancer Antigensmentioning
confidence: 99%